Empirical perspectives in capital asset pricing - Galagedera, Don U. A. (Managerial finance, 2007)
Increased globalization and economic integration among economies of the world has brought increased attention of investors and academic scholars to the issue of interrelationships among capital markets around the world. Particularly, the interest has been heightened by increased flows of capital across countries which, in turn, are primarily explained by market deregulation measures, technological improvements, and innovations of different financial products. The increasingly closer relationship among international financial markets and the increasing international portfolio investment have im.